Employee Engagement, Organizational Citizenship Behavior, and Work Ethic as Antecedent Variables of Employee Performance - Yocaruci Aulia Ardita Venidico; Endang - Sulistiyani; Erika - Devi (Admisi dan Bisnis, 2022)
PT Jasco Logistic Semarang is one of the companies engaged in the field of freight forwarding. The purpose of this study was to determine the effect of employee engagement, organizational citizenship behavior (OCB), and work ethics on employee performance at PT Jasco Logistic Semarang. Data collection methods used were interviews, literature study, and questionnaires distributed to 31 respondents with a sampling method that is saturated sample. Data analysis methods include validity test, reliability test, classic assumption test, T test, F test, and coefficient of determination. The results showed that employee engagement, organizational citizenship behavior (OCB), and work ethics have a joint influence on employee performance. Based on the coefficient of determination test, the value on the Adjusted R Square is 0.802, which means the contribution of the independent variable to the dependent variable is 80.2% while the remaining 0.198 or 19.8% is influenced by other variables not examined in this study.